Racism and Anti-Racism in Football - Garland, Jon. author. aut Link
VIII, 223 p.
Keywords: This book explores the key issues of racism, anti-racism and identity in British football. It relates the history of black players in the game, analyses the racism they have experienced, and evaluates the efficacy of anti-racist campaigns. The efficacy of the policing of racism is also assessed. The nationalism and xenophobia evident in much of the media's coverage of major tournaments is highlighted in the context of the way that English, Scottish and Welsh identities are constructed within British football.